Role of 3‐D conformal radiotherapy for major portal vein tumor thrombosis combined with hepatic arterial infusion chemotherapy for advanced hepatocellular carcinoma. Issue 6 (19th August 2014) - Fujino, Hatsue; Kimura, Tomoki; Aikata, Hiroshi; Miyaki, Daisuke; Kawaoka, Tomokazu; Kan, Hiromi; Fukuhara, Takayuki; Kobayashi, Tomoki; Naeshiro, Noriaki; Honda, Yohji; Tsuge, Masataka; Hiramatsu, Akira; et al.
<x xml:space="preserve">Abstract</x> Aim To evaluate the response, survival and safety on 3‐D conformal radiotherapy (3D‐CRT) for major portal vein tumor thrombosis (PVTT) combined with hepatic arterial infusion chemotherapy (HAIC) for advanced hepatocellular carcinoma (HCC). Methods In this retrospective study, 83 advanced HCC patients treated with HAIC who met the following criteria were enrolled: (i) PVTT of the main trunk or first branch of the portal vein; (ii) no extrahepatic metastasis; (iii) Child–Pugh score of 5–7; (iv) performance status of 0 or 1; and (v) no history of sorafenib treatment. The response, overall survival (OS), time to treatment failure (TTF), post‐progression survival (PPS) and safety were compared between HAIC combined with 3D‐CRT for PVTT (RT group, n = 41) and HAIC alone (non‐RT group, n = 42). Results The objective response of PVTT was significantly higher in the RT group (56.1%) than in the non‐RT group (33.3%), while that of intrahepatic tumor and OS were not significantly different between groups. Median OS, TTF and PPS were significantly longer in the RT group than in the non‐RT group (8.6 and 5.0 months, 5.0 and 2.7 months, and 5.3 and 1.5 months, respectively) among intrahepatic tumor non‐responders to HAIC, whereas those were not significantly different between groups among intrahepatic tumor responders to HAIC. By multivariate analysis, the combination of 3D‐CRT with HAIC was an independent contributing factor for OS (hazard ratio, 3.2; 95% confidence interval, 1.692–6.021; P < 0.001) among intrahepatic HCC non‐responders to HAIC. Conclusion 3D‐CRT for PVTT combined with HAIC could provide survival benefit to non‐responder to HAIC.